Rough sets theory and uncertainty into information system - Jirava, Pavel (Univerzita Pardubice, 2006)
This article is focused on rough sets approach to expression of uncertainty into information system. We assume that the data are presented in the decision table and that some attribute values are lost. At first the theoretical background is described and after that, computations on real-life data are presented. In computation we wok with uncertainty coming from missing attribute values.
Keywords: Informační systémy; hrubé množiny; rough sets; neurčitost